2008
DOI: 10.1111/j.1365-2141.2007.06958.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric myelodysplastic syndromes and juvenile myelomonocytic leukaemia: molecular classification and treatment options

Abstract: SummaryMyelodysplastic syndromes (MDS) and the mixed myelodysplastic/myeloproliferative disorder juvenile myelomonocytic leukaemia (JMML) are rare haematopoietic stem cell diseases in children. While MDS-initiating events remain largely obscure, a growing body of clinical, genetic and laboratory evidence suggests that JMML is, at least in part, caused by aberrant signal transduction resulting from mutations of components of the RAS signalling pathway. To date, haematopoietic stem cell transplantation cures mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
131
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 117 publications
(148 reference statements)
1
131
0
1
Order By: Relevance
“…Our data therefore support and extend previous notions that molecular alterations in the RAS-MAPK/ERK pathway are associated with a monocytic subtype, in both AML 8,53 and myelodysplastic/myeloproliferative neoplasms such as chronic and juvenile myelomonocytic leukemia. 54,55 Gene expression data were available in the cohort of 285 AML patients and reduced RKIP expression was mainly confined to a specific cluster of samples ('cluster 5' in Valk et al 21 ). This cluster comprises almost exclusively patient samples with a monocytic subtype but has not been characterized by a recurrent molecular alteration so far.…”
Section: Discussionmentioning
confidence: 99%
“…Our data therefore support and extend previous notions that molecular alterations in the RAS-MAPK/ERK pathway are associated with a monocytic subtype, in both AML 8,53 and myelodysplastic/myeloproliferative neoplasms such as chronic and juvenile myelomonocytic leukemia. 54,55 Gene expression data were available in the cohort of 285 AML patients and reduced RKIP expression was mainly confined to a specific cluster of samples ('cluster 5' in Valk et al 21 ). This cluster comprises almost exclusively patient samples with a monocytic subtype but has not been characterized by a recurrent molecular alteration so far.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] JMML is characterized by 'spontaneous' proliferation of marrow and peripheral blood mononuclear cells in vitro with exuberant growth of granulo-macrophage colonies in the absence of exogenous growth factors, because of a selective hypersensitivity of the hematopoietic precursor cells to granulocyte macrophage colony-stimulating factor (GM-CSF). 4 Deregulation of GM-CSF signal transduction is driven by the RAS pathway because of oncogenic mutations in N-RAS, K-RAS, or PTPN11 genes or inactivation of the NF1 tumor suppressor gene.…”
mentioning
confidence: 99%
“…Mutations of NF1, NRAS, KRAS and PTPN11 genes are found in approximately 70% of JMML patients, and are implicated in the aberrant RAS signaling. 1 On the other hand, the remaining approximately 30% of JMML patients have no known mutations.…”
mentioning
confidence: 99%
“…1 In a Cancer and Leukemia Group B study, isolated trisomy 11 was identified in 13 cases (0.9%) among 1496 consecutive adult patients with AML. 2 The majority of the patients with isolated trisomy 11 were older than 60 years and 46% achieved a complete remission after induction chemotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation